Cellular Debris in the Anterior Vitreous in Silent Eyes of Behçet Patients as a Clue of Asymptomatic Ocular Involvement - Abdullah Kursat Cingu; Fatih Mehmet Türkcü; Bariş Yeniad; llknur Tugal-Tutkun (Journal of Ophthalmology)
Purpose. To investigate if there is a prognostic implication of the presence of cellular debris in the anterior vitreous in patients with Behçet's disease (BD) without any ocular symptoms. Methods. One hundred and twenty eyes of 60 patients with BD were included in the study. The eyes were divided into two groups according to the presence of cellular debris in the anterior vitreous. The first group included 54 eyes which were cellular debris (+) (group A), and the second group included 66 eyes which were cellular debris (−) (group B). Fluorescein angiography (FA) was performed to all patients following routine ocular examination. Patients were called for the six monthly control visits to investigate possible new ocular involvement during followup. The Kaplan-Meier method was used to estimate survival curves. Results. Seven eyes (13%) in group A and four eyes (6.1%) in group B showed optic disc hyperfluorescence on FA (). None of the eyes with disc hyperflourescence on initial examination developed uveitis attacks in their followup. In Kaplan-Meier survival analysis there was a significant difference between the groups (group A 20.6% and group B 4.2%) by means of ocular involvement during their followup (log-rank = 6.85, ). Conclusions. Presence of cellular debris in the anterior vitreous may have prognostic implications in patients with BD screened for ocular involvement.